FAKTOR FAKTOR YANG MEMPENGARUHI SUKU BUNGA KREDIT INVESTASI PADA SEKTOR PERBANKAN DI INDONESIA PERIODE 2006-2012 - Thomas Budi Setianto (MIX: JURNAL ILMIAH MANAJEMEN, 2013)
Abstract: This paper has a purpose to know about influence of the macroeconomicfactors are BI rate, inflation, money supply and exchange rate opposite investation creditinterest rate. The analysis used multiple linear regression with study period January2006–December 2012. Empirical test result prove that variable of the policy interest rateBI has a major impact or influence the development of investation credit interest rate.Variable of inflation and money supply have no significant contribution influence in themovement of the investation credit interest rate. And variable of exchange rate rupiahopposite of US dollar has little contribution with opposite effect in influencingmovement of investation credit interest rate.Keywords: BI rate, inflation, money supply, exchange rate, invest credit interest rate.